Selected Issues of Incorporation and Implementation of Norms of Private International Law into National and EU Law (Based on Transport Agreement Regulations) - Krzysztof Wesolowski (Communications of International Proceedings, 2020)
In some areas of private law a certain convergence of regulations applicable in different systems (bodies) of law can be observed. One of such domains is the transport law where, for many years now, a process of interpenetration of legal concepts and entire regulations has been noticed. It can take the form of, i.a., incorporation and implementation of regulations drawn from a different system of law. Each of these two methods has its strengths and weaknesses. The issue of incorporation and implementation of norms set out in international transport conventions into the EU law is particularly interesting. It is connected with regulations issued by the EU institutions with the aim to improve the legal status of passengers using various modes of transportation. The regulations were designed to supplement and modify the norms resulting from international conventions in order to enhance and protect passenger’ rights. However, conventions are transposed into the EU law using different methods, different from the ones applied in national law. This gives rise to specific problems. The aim of the paper is to identify the problems and also the benefits and drawbacks of the solutions adopted. The research method used by the author include analysis of legal acts, case law and secondary literature.
Keywords: International Uniform Private Law; Incorporation; Implementation; Transport Law